The relationship between physical work environment and employees’ work performance at Amanah Saham Nasional Berhad, Temerloh / Nur Syahiera Mohamed Yusof - Mohamed Yusof, Nur Syahiera (2020)
This study attempts to shows the relationship between physical work environment and employees’ work performance at Amanah Saham Nasional Berhad, Temerloh. The indepenedent variables use in this researches was physical work environment consist of Office Lighting, Office Furniture, Office Noise and Office Air Quality. Meanwhile the dependent variable was employees’ work performances. The problems statement is this research was attempts to identify the relationship between physical work environment and employees’ work performance at Amanah Saham Nasional Berhad, Temerloh. Berhad (ASNB), Temerloh. The researcher uses the questionnaire to collect the data in this research. Therefore, the questionnaires were distributed to all employees by departments at Amanah Saham Nasional Berhad, Temerloh. The respondents that answer the questions are 44 from 50 respondents. This research would show the result of factors and relationship between physical work environment and employees’ work performance. The analysis that used in this research were reliability analysis, normality analysis, demographic analysis and finding based on the the research questions. All the result is using the SPSS software version 25